Sensitivity of the 2018 UK summer heatwave to local sea temperatures and soil moisture. (3rd January 2020) - Petch, Jon C.; Short, Chris J.; Best, Martin J.; McCarthy, Mark; Lewis, Huw W.; Vosper, Simon B.; Weeks, Mark
Abstract: The impact of local climate conditions on air temperatures during a hot summer period over the United Kingdom in 2018 is studied using simple sensitivity experiments with a state‐of‐the‐art regional numerical weather prediction system. The experiments are designed to investigate the influence of sea surface temperature (SST) and soil moisture on the air temperatures over land. They involved applying changes to the analysed SST and soil moisture patterns with magnitudes consistent with the differences between forecast analysis and climatology. The results from daily 5‐day forecasts over an 11‐day period show that a 3°C reduction in SSTs reduces the simulated air temperatures averaged over all land points by just over 1°C. Moistening the soil while using the control SSTs reduces the temperatures by a little less than 1°C on average although this can be larger than 3°C locally. While the reduction in SST impacts the daily maximum and minimum temperatures to a similar extent, the increase in soil moisture had little impact on the daily minimum temperatures. Abstract : Weather forecasting simulations are used to study the impact of local climate conditions on the 2018 UK heatwave. Focusing on an 11‐day period it is shown that changes in sea surface temperatures (SSTs) and soil moisture can change forecast temperatures by about 1°C. The impacts of soil moisture changes were more spatially variable than those of SSTs and predominantly influenced maximum temperatures.